2019
DOI: 10.1021/acs.inorgchem.8b03035
|View full text |Cite
|
Sign up to set email alerts
|

Glycans as Ligands in Bioinorganic Chemistry. Probing the Interaction of a Trinuclear Platinum Anticancer Complex with Defined Monosaccharide Fragments of Heparan Sulfate

Abstract: We report herein a detailed NMR study of the aquation and subsequent covalent binding of the trinuclear clinical agent [{trans-PtCl( 1 5 NH 3 ) 2 } 2 {μ-trans-Pt-( 15 NH 3 ) 2 ( 15 NH 2 (CH 2 ) 6 15 NH 2 ) 2 }] 4+ (1, 1,0,1/t,t,t or Triplatin) with three D-glucosamine residues containing varied O-sulfate and N-sulfate or N-acetyl substitutions, which represent monosaccharide fragments present within the repeating disaccharide sequences of cell surface heparan sulfate (HS). The monosaccharides GlcNS(6S), GlcNS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…[44] Ap olyamine-linked Pt IV compound displays interesting anti-metastatic properties upon proposed reduction to Pt II and polyamine release. [45] Indeed, in the absence of aPt-Cl bond for covalent binding to target biomolecules, [46] the substitution-inert PPCs do have some similarities with polyamines.S permine itself binds to and modifies the structure of HS with effects on polyamine pathways. [47] In both solution and gas-phase DNAb inding studies,c omplexes such as Tr iPtNC have significantly higher affinity than the simple polyamines and are significantly more effective DNA-condensing agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Ap olyamine-linked Pt IV compound displays interesting anti-metastatic properties upon proposed reduction to Pt II and polyamine release. [45] Indeed, in the absence of aPt-Cl bond for covalent binding to target biomolecules, [46] the substitution-inert PPCs do have some similarities with polyamines.S permine itself binds to and modifies the structure of HS with effects on polyamine pathways. [47] In both solution and gas-phase DNAb inding studies,c omplexes such as Tr iPtNC have significantly higher affinity than the simple polyamines and are significantly more effective DNA-condensing agents.…”
Section: Resultsmentioning
confidence: 99%
“…A polyamine‐linked Pt IV compound displays interesting anti‐metastatic properties upon proposed reduction to Pt II and polyamine release [45] . Indeed, in the absence of a Pt‐Cl bond for covalent binding to target biomolecules, [46] the substitution‐inert PPCs do have some similarities with polyamines. Spermine itself binds to and modifies the structure of HS with effects on polyamine pathways [47] .…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the comparison of phosphate and sulfate [35] shows that the rate constant for sulfate displacement of the aqua ligand (kL) is approximately 3-fold higher than that of phosphate, whilst aquation of the bound sulfato ligand (k-L) is more than an order of magnitude faster in comparison to displacement of phosphate. The reaction of the trinuclear 1,0.1/t,t,t with sulfate similarly reaches equilibrium after 12 h and has a similar distribution at equilibrium of chloro, aqua and sulfato species [36]. However, inspection of the rate constants (Table 2) shows interesting differences attributed to a balance of ion-pairing (Cl -) and/or formation of "sulfate clamps" with the charged central {PtN4} 2+ unit.…”
Section: < Insert Table 2 and Scheme 1 Here>mentioning
confidence: 96%
“…To understand the kinetics of covalent binding with the monosaccharide fragments that represent those present within the repeating disaccharide units of HS, we have used 2D [ 1 H, 15 N] HSQC NMR spectroscopy to follow the interaction of 15 N-labelled 1,0,1/t,t,t with three D-glucosamine residues (GlcNS(6S), GlcNAc(6S) and GlcNS; see Fig. 7c) containing varied O-sulfate and N-sulfate or N-acetate substitutions at 6-O and/or 2-N positions [36]. The conditions were similar to those previously used for the reactions with anionic systems (see section 4).…”
Section: Interaction Of Polynuclear Platinum Complexes With Defined Fragments Of Heparan Sulfatementioning
confidence: 99%
“…For example, we have investigated the interaction of the trinuclear (Triplatin or 1,0,1/t,t,t) and dinuclear (1,1/t,t) PPCs with three D-glucosamine residues containing varied O-sulfate and N-sulfate or N-acetyl substitutions, which represent monosaccharide fragments present within the repeating disaccharide sequences of cell surface heparan sulfate. 9 We have studied also the interaction of these PPCs with 1,2-dihexanoyl-sn-glycero-3-phosphate (DHPA), a shorter, water-soluble model for the phospholipid DPPA (Chart 1). 10 These latter studies showed that the monofunctional DHPA adduct of 1,1/t,t coordinated to a second DHPA molecule in two different orientations, leading to formation of two conformers of the bifunctional adduct.…”
Section: Introductionmentioning
confidence: 99%